Immune‐related adverse events predict responses to PD‐1 blockade immunotherapy in hepatocellular carcinoma. Issue 4 (5th May 2021) - Lu, Lianghe; Xing, Kaili; Wei, Wei; Ling, Yihong; Li, Peng; Li, Shaohua; Wang, Yan; Xie, Dan; Guo, Rongping; Cai, Muyan
Abstract: Immune checkpoint blockade has demonstrated remarkable efficacy in hepatocellular carcinoma (HCC) but is also commonly accompanied by immune‐related adverse events (irAEs). However, the association between irAEs and antitumor efficacy in HCC patients remains unknown. All patients with HCC treated with anti‐PD‐1 antibodies from July 2018 to November 2019 were analyzed and divided into different groups according to their irAEs' status. In total, 101 HCC patients, including 21 (20.8%) patients who presented with irAEs (irAEs + ), were enrolled. Among the adverse events, rash (n = 9, 8.9%) was the most frequent irAE, followed by mucositis (n = 3, 3.0%) and thyroiditis (n = 3, 3.0%). Patients in the irAEs + group showed a higher tumor response rate than those in the irAEs − group (overall response rate: 28.6% vs 6.3%, P  = .011; disease control rate: 85.7% vs 60.0%, P  = .028). The median progression‐free survival (PFS) times were 14.8 months in the irAEs + group and 4.1 months in the irAEs − group ( P  < .001). Further analysis based on the presence or absence of rash showed that the PFS of the patients in the irAEs + /rash + group was better than that of those in the irAEs + /rash − or irAEs − group (all P  < .05). Multivariate analysis showed that irAEs were an independent prognostic factor for PFS (hazard ratio [HR]: 0.22, P  = .002). Thus, the occurrence of irAEs, especially rash, was associated with markedly improved PFS. Awareness of irAEs may help classify the subtype of HCC patients with an unprecedented survival benefit from anti‐PD‐1 antibodies. Abstract : What's new? While anti‐program death receptor‐1 (anti‐PD‐1) antibodies produce clinical responses in patients with hepatocellular carcinoma (HCC), variations in efficacy and in the occurrence of adverse events present significant challenges in the clinical management of HCC. In the present study, the authors show that in HCC patients treated with anti‐PD‐1 antibodies, the development of immune‐related adverse events (irAEs), notably rash, is associated with improved progression‐free survival. The marked association between irAEs and treatment response suggests that irAEs could be used to predict survival in anti‐PD‐1 antibody‐treated HCC patients and could facilitate HCC subtype classification in patients who experience striking survival benefits.